Homocysteine inhibits neural stem cells survival by inducing DNA interstrand cross-links via oxidative stress. (2nd December 2016) - Wang, Dan; Chen, Yi-ming; Ruan, Miao-hua; Zhou, Ai-hua; Qian, Yan; Chen, Chao
Highlights: Hcy inhibits neural stem cells survival. Hcy causes cell interstrand cross-links by oxidative stress and activates FA pathway. Inhibiting Hcy-envoked reactive oxidative species generation could ameliorate DNA damage and cell survival. Abstract: Elevated plasma levels of homocysteine have been implicated in neurodevelopmental and neurodegenerative disorders in human studies. Although the molecular mechanisms underlying the effects of homocysteine (Hcy) cytotoxicity on the nervous system are not yet fully unknown, induction of DNA interstrand cross-links and inhibition of neural stem cells (NSCs) survival may be involved. The objective of our study was to investigate the effects of Hcy on DNA interstrand cross-links in NSCs, and to explore its possible mechanisms. We also found that Hcy induced cell DNA damage on a dose-dependent manner and evoked reactive oxidative species (ROS) production, leading to elevated apoptosis in NSCs. Moreover, Hcy exposure activated the Fanconi anemia (FA) pathway, which was characterized by increases in monoubiquitination of Fanci and Fancd2 and enhancement of the interaction between above two proteins. On contrary, N -Acety-l -Cysteine (NAC) decreased Hcy-evoked ROS production and significantly ameliorated DNA damage and improved cell survival. These data suggest that Hcy may play a role in the pathogenesis of neurological diseases via a molecular mechanism that induces DNA interstrand cross-links via oxidative stress and involves in negative regulation of NSCs survival.